Evaluating global interest in biodiversity and conservation - Caetano Oliveira de Henrique Gabriel; Vardi Reut; Jarić Ivan; Correia A. Ricardo; Roll Uri; Veríssimo Diogo (Wiley-Blackwell Publishing, Inc., 2026)
The first target of the Convention for Biological Diversity (Aichi target 1) was to increase public awareness towards the values of biodiversity and actions needed to conserve it - a key prerequisite for other conservation targets. Monitoring success in achieving this target at a global scale has been difficult until recently. However, the increased digitization of human life in recent decades offers insight into people's interests at an unprecedented scale, which allows a more comprehensive evaluation of success towards Aichi target 1 than previously attempted. Here, we used Google search volume data to evaluate global interest in biodiversity and its conservation; and investigated their correlates across countries. We found that during 2013–2020 global searches for biodiversity increased, driven mostly by searches for charismatic fauna. However, searches for conservation actions, driven mostly by searches for national parks, decreased since 2019 likely due to the COVID-19 pandemic. We further found that economic inequality was negatively correlated with interest in biodiversity and conservation, while purchasing power was indirectly positively correlated through increased education and research. Our results suggest partial success towards achieving Aichi target 1, in that interest in biodiversity has increased widely, but not for conservation. We suggest that increased outreach and education efforts towards neglected aspects of biodiversity and conservation are still needed. Popular topics in biodiversity and conservation could be leveraged to increase awareness of other topics, with attention to local socioeconomic contexts.